Participation in and contents of two dutch political party discussion lists on the internet - Hagemann, Carlo (Javnost (Ljubljana), 2002)
This study examines two political discussion lists affiliated with the Dutch political parties D66 and GroenLinks, and the possible contribution of these lists to democracy. Discussion in a democracy, it is argued, should be deliberative: based on rational argumentation, not monopolised by any particular individuals, and related to public affairs. The aim of this study is to assess the deliberativeness of political discussion lists on the Internet. To this end, the degree of contribution from participants to the lists is measured. The findings from this study suggest that, whereas the discussions on the lists as a whole were not monopolised by any individual, both lists had only a small number of very frequent participants. The contributions of members of this in-group were oriented towards one another. Opinions were mainly expressed without argumentation, and when argumentation was given it was predominantly based on common sense or on external sources such as newspapers or teletext. These two discussion lists do not live up to the expectations of furthering democracy. They may, however, eventually serve to fill the gap between the institutionalised public discussion that exists within the party elite and the uninstitutionalised, informal public discussion that transpires in other public and private domains.
Keywords: Nizozemska; political party; politične stranke; komuniciranje; communication; politične komunikacije; računalniške komunikacije; internet